Imam Al-Ghazali's Approach to the Authority of AL– Qiyas (Analogical Reasoning) Fundamentalist Analytical Study - AL- Badawi , Nidaa Khalid Walid (Dirasat: Shari'a and Law Sciences, 2021)
This study deals with clarifying and highlighting Imam Al-Ghazali's approach to proving the authenticity of measurement through his fundamentalist books, dealing with evidence, proofs and discussions that differed from the approaches of other fundamentalists. The study used the descriptive method by collecting information from the fundamentalist books of Al-Ghazali and other fundamentalist books, in addition to the books of the fundamentals of comparative jurisprudence, books related to the fundamentalist methods and the inductive method by looking at the collected material, extrapolating it and making observations on it, and the analytical method by analyzing and comparing this information, and employing it to serve the research of the study, and to achieve the desired goals. The study concluded a number of results, the most prominent of which is Imam Al-Ghazali's consideration of Qiyas as a kind of arrest, which he proved by relying on the general vowel, the moral generality, and the habit of the street, which makes his approach to establishing authenticity a unique approach that distinguishes him from the rest of the fundamentalists. The study recommended the need for continuous attention to the study of fundamentalist curricula to benefit from the ideas contained therein. Researchers should also expand their Ijtihad view and follow the example of Imam Al-Ghazali in how he continuously develops his fundamentalist path..